(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The research focuses on the interests involved in influencing public opinion both within one's own country and abroad. The advancement of globalisation and the intensification of informational connectivity make this topic increasingly relevant in the information-dominated world of the 21st century. Malicious access to the attitudes and sentiments of individuals is understood as a challenge to national security. The aim of the study is to uncover the broad scope, potential and the key factors involved in contemporary competition for access to public opinion, as well as some differences in state-level strategies. The focus is set on the cyberspace and on informational interventions, identified as a defining factor in today's international security landscape. The methodology is based on comparison and generalisation. The scientific approach is phenomenological. Accessible data has been used to define vectors for the presence of states in cyberspace. These are: software, hardware, and technologies, as well as artificial intelligence. Following a theoretical analysis, three defining vectors for public opinion were identified: mobility, ideological environment, and informational accessibility. A comparative analysis of the interdependencies between the identified vectors was carried out, considering the US, Russia, the UK, and the EU, as states of interest in international security. The analysis also includes the interests from cyberspace as an independent participant in this competitive interaction. The work reveals differences in the strategic approaches to accessing public opinion and to protecting it from unwanted manipulations. Furthermore, the study shows that, despite the differences, the competition for access to the attitudes and sentiments of individuals is associated with high costs, which are exhausting for society. The primary conclusion reached is that the competitive actions of the analysed actors resemble a New Cold War, fought for access to influence over public opinion in states. It is emphasised that in this New Cold War, more than two centres of influence are emerging. They "fight" in different ways, but resistance is inevitable and increasingly requires greater material and societal potential.